2015
DOI: 10.5603/fhc.a2018.0004
|View full text |Cite
|
Sign up to set email alerts
|

Epac1 is involved in cell cycle progression in lung cancer through PKC and Cx43 regulation

Abstract: Normal Epac1 expression may suppress lung cancer occurrence and metastasis, and its downregulation is involved in cell cycle progression in lung cancer through PKC and Cx43 regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Mammalian exchange protein directly activated by cAMP isoform 1 (EPAC1), encoded by RAPGEF3 gene, acts as guanine exchange factor for Ras-like Rap small GTPases [39]. EPAC1 expression was lower in lung cancer tissue compared to expression in normal specimens and associated with the degree malignancy and lymph-node metastasis [40]. SGK is one of three isoforms of the serum glucocorticoid regulated kinase family of serine/threonine kinases.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian exchange protein directly activated by cAMP isoform 1 (EPAC1), encoded by RAPGEF3 gene, acts as guanine exchange factor for Ras-like Rap small GTPases [39]. EPAC1 expression was lower in lung cancer tissue compared to expression in normal specimens and associated with the degree malignancy and lymph-node metastasis [40]. SGK is one of three isoforms of the serum glucocorticoid regulated kinase family of serine/threonine kinases.…”
Section: Discussionmentioning
confidence: 99%
“…[16] CX43 , as a member of CX family, was alleviated in a few of solid tumors, including breast cancer, [17] ovarian cancer, [18] and lung cancer. [19] In our previous study, we found that CX43 was highly expressed in BC tissues. [5,20] Once again, we verified that CX43 might be a potential target for BC treatment.…”
Section: Discussionmentioning
confidence: 99%